The Use of Serial Image Media to Improve The Ability to Retell The Contents of Fairy Tales to Third Grade Students of SDN Malabar 01 - Nene Rokaesih (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The study was entitled "The use of serial image media to improve the ability to retell storytelling content to third grade students of SDN Malabar 01 in the academic year 2020/2021".Aimed at knowing the increase in student interest and learning achievement in Indonesian language learning material Picture Series in class III SDN Malabar 01, Wanareja District.The object of the research was the third grade students of SDN Malabar 01, Wanareja sub-district, Cilacap district, with a total of 19 students. The procedure for implementing learning improvement with classroom action research is divided into three cycles. This research is focused on problems related to student interest and achievement through Thinkpair and share methods. Data obtained using observation, and test. The criteria for the success of this study can be seen from the increased interest and achievement of student learning outcomes from cycle I to cycle II and cycle II to cycle III.